STUDI SOSIOLINGUISTIK ALIH KODE DAN CAMPUR KODE BAHASA PAKSEL (NGAPAK JAKSEL) DALAMVIDEO TIKTOKRAFLY - Rahayu, Feri Kanti; Festiyanti, Wilda Putri (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2024)
“Language is a form of communication to convey information, thoughts, feelings, and goals or intentions to other people. In the era of globalization, the use of more than one language is often experienced by someone who is called a